2007
DOI: 10.1016/j.pnpbp.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric alterations of the orbitofrontal cortex in autism

Abstract: Recent evidence has implicated the orbitofrontal cortex (OFC) in the pathophysiology of social deficits in autism. An MRI-based morphometric study of the OFC was conducted involving 11 children with autism (age range 8.1-12.7 years) and 18 healthy, age-matched controls (age range 8.9-12.8 years). Decreased grey matter volume in the right lateral OFC in the patient group was found, and correlations were observed between social deficits and white, but not grey, matter structures of the OFC. These findings suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 35 publications
(36 reference statements)
3
55
1
1
Order By: Relevance
“…More importantly, impairment in object reversal learning also follows neonatal damage to the orbital frontal cortex in monkeys (see for review Goldman-Rakic, Isseroff, Schwartz, & Bugbee, 1983) suggesting that dysfunction of the orbital frontal cortex could occur in early infancy in people with autism. This proposal is supported by recent volumetric studies (Girgis, Minshew, Melhem, Nutche, Keshavan, & Hardan, 2007;Hardan, Girgis, Lacerda, Yorbik, Kilpatrick, Keshavan, & Minshew, in press) demonstrating decreased volume of the right lateral orbital frontal cortex (white plus grey matter) in people with autism, and in one of these studies (Girgis et al, 2007) the changes were correlated with social deficits.…”
Section: Tasks Measuring Functions Of the Orbitofrontal-amygdala Circuitmentioning
confidence: 59%
“…More importantly, impairment in object reversal learning also follows neonatal damage to the orbital frontal cortex in monkeys (see for review Goldman-Rakic, Isseroff, Schwartz, & Bugbee, 1983) suggesting that dysfunction of the orbital frontal cortex could occur in early infancy in people with autism. This proposal is supported by recent volumetric studies (Girgis, Minshew, Melhem, Nutche, Keshavan, & Hardan, 2007;Hardan, Girgis, Lacerda, Yorbik, Kilpatrick, Keshavan, & Minshew, in press) demonstrating decreased volume of the right lateral orbital frontal cortex (white plus grey matter) in people with autism, and in one of these studies (Girgis et al, 2007) the changes were correlated with social deficits.…”
Section: Tasks Measuring Functions Of the Orbitofrontal-amygdala Circuitmentioning
confidence: 59%
“…Thus, under these conditions, the current findings in high functioning children with autism may suggest impairments in voluntary or controlled orienting of attention. There is evidence in the autism literature to support the suggestion of impairments in the executive control of attention in autism (e.g., Geurts et al 2004;Goldberg et al 2005;Hughes et al 1994;Landa and Goldberg 2005;Ozonoff 1997;Ozonoff et al 1991Ozonoff et al , 2004Pennington and Ozonoff 1996) as well as differences in frontal lobe regions of the brain in individuals with autism (e.g., Bailey et al 1998;Carper and Courchesne 2000;Girgis et al 2007;Kemper and Bauman 1998;Ohnishi et al 2000;Zilbovicius et al1995). Posner (1988Posner ( , 1990 described three mechanisms involved in orienting attention on cueing tasks: attention must be disengaged from the current location, moved to a cued location, and then engaged in a target or stimulus at the new location.…”
Section: Discussionmentioning
confidence: 97%
“…The OFC is also involved in stimulus-reinforcement association learning, including the association of olfactory stimuli and the primary reinforcement value of taste (67). Several groups have proposed dysfunction in OFC or OFC-amygdala circuitry in autism (18,68,69), and recent neuroimaging studies reported evidence of developmental abnormalities in OFC volume (70,71).…”
Section: Discussionmentioning
confidence: 99%